2006
DOI: 10.1037/0096-1523.32.3.633
|View full text |Cite
|
Sign up to set email alerts
|

Semantic activation in action planning.

Abstract: Four experiments investigated activation of semantic information in action preparation. Participants either prepared to grasp and use an object (e.g., to drink from a cup) or to lift a finger in association with the object's position following a go/no-go lexical-decision task. Word stimuli were consistent to the action goals of the object use (Experiment 1) or to the finger lifting (Experiment 2). Movement onset times yielded a double dissociation of consistency effects between action preparation and word proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
97
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 67 publications
12
97
1
Order By: Relevance
“…Tucker and Ellis (2004) demonstrated that showing a graspable object's name produced a congruency effect on manual responses similar to the one commonly registered in visual object categorization studies. Similar effects were reported in Bub, Masson, and Cree (2008) for both functional (grasping) and volumetric (lifting) actions (see also Lindemann et al, 2006). Interestingly, while elicitation of affordance effects from observing objects may be bound by the limits of reachable space, objects' names can act as activation cues to stimulus-response compatibility effects for objects within and outside of reachable space (Ferri et al, 2011).…”
Section: Visual and Linguistic Cues To Manual Grasp Affordancesmentioning
confidence: 55%
“…Tucker and Ellis (2004) demonstrated that showing a graspable object's name produced a congruency effect on manual responses similar to the one commonly registered in visual object categorization studies. Similar effects were reported in Bub, Masson, and Cree (2008) for both functional (grasping) and volumetric (lifting) actions (see also Lindemann et al, 2006). Interestingly, while elicitation of affordance effects from observing objects may be bound by the limits of reachable space, objects' names can act as activation cues to stimulus-response compatibility effects for objects within and outside of reachable space (Ferri et al, 2011).…”
Section: Visual and Linguistic Cues To Manual Grasp Affordancesmentioning
confidence: 55%
“…We expected the time to initiate reaching to be shorter when it was cued by an object affording the same type of grip rather than a different type of grip, that is, an object affordance effect (Tucker & Ellis, 2001). Taking into account previous research showing an impact of semantic magnitude information on grasping kinematics Lindemann, Abolafia, Girardi, & Bekkering, 2007;Lindemann, Stenneken, van Schie, & Bekkering, 2006), we also expected the perceived object size to affect the aperture of the hand during the reaching phase, as revealed by an enlarged MGA for pictures of large as compared with small objects.…”
Section: Methodsmentioning
confidence: 99%
“…It assumes that cognitive processes are grounded in perception and action (Barsalou, 1999). Ample evidence for the embodied cognition framework comes from psychological research in a variety of domains, such as research on action semantics (e.g., Lindemann, Stenneken, Van Schie, & Bekkering, 2006), language comprehension (e.g., Zwaan & Taylor, 2006), and neuroscience (e.g., Glenberg et al, 2008). This research shows that visual and motor processes in the brain are active during the performance of cognitive tasks such as reading, comprehension, mental arithmetic, and problem solving, while semantic codes are activated during the performance of motor tasks, suggesting that cognitive and sensorimotor processes are closely intertwined.…”
Section: Effects Of Part-body Movementsmentioning
confidence: 99%